RUSSIAN UNIVERSITIES IN THE MARKET OF EDUCATIONAL SERVICES - K. Balkizova (Вестник университета)
The article discusses the position of Russia and Russian universities on the world market of educational services. The analysis of the basic methods of Russian universities on the foreign markets. Strategies of Russian universities, in addition to the participation in exchange programs and joint educational programs include the establishment of foreign branches and the formation of the joint universities abroad. Little-used Russian universities the potential of distance education to attract foreign students, and other strategies, for example, the franchising of education, are not used abroad.